Nanoscale Heterogeneity of Multilayered Si Anodes with Embedded Nanoparticle Scaffolds for Li‐Ion Batteries - Haro, Marta (Adv Sci (Weinh), 2017)
A new approach on the synthesis of Si anodes for Li‐ion batteries is reported, combining advantages of both nanoparticulated and continuous Si films. A multilayered configuration prototype is proposed, comprising amorphous Si arranged in nanostructured, mechanically heterogeneous films, interspersed with Ta nanoparticle scaffolds. Particular structural features such as increased surface roughness, nanogranularity, and porosity are dictated by the nanoparticle scaffolds, boosting the lithiation process due to fast Li diffusion and low electrode polarization. Consequently, a remarkable charge/discharge speed is reached with the proposed anode, in the order of minutes (1200 mAh g(−1) at 10 C). Moreover, nanomechanical heterogeneity self‐limits the capacity at intermediate charge/discharge rates; as a consequence, exceptional cycleability is observed at 0.5 C, with 100% retention over 200 cycles with 700 mAh g(−1). Higher capacity can be obtained when the first cycles are performed at 0.2 C, due to the formation of microislands, which facilitate the swelling of the active Si. This study indicates a method to tune the mechanical, morphological, and electrochemical properties of Si electrodes via engineering nanoparticle scaffolds, paving the way for a novel design of nanostructured Si electrodes for high‐performance energy storage devices.